THE PEDAGOGICAL SIGNIFICANCE AND PROFESSIONAL NECESSITY OF DEVELOPING CREATIVE ABILITIES IN FUTURE EDUCATORS - Julmanova Saodat (International Scientific and Current Research Conferences, 2023)
Creativity is an essential skill for educators in the 21st century, enabling them to foster innovation, adapt to diverse classroom needs, and inspire their students. This article explores the pedagogical significance and professional necessity of developing creative abilities in future educators. It examines how creativity enhances teaching practices, supports problem-solving, and aligns with modern educational demands. Key strategies for fostering creativity in teacher education programs are discussed, including experiential learning, interdisciplinary approaches, and reflective practices. The article also highlights challenges in developing creativity and offers recommendations for integrating creative training into teacher preparation programs.